Implementing Neuromarketing in the Enterprise: Factors That Impact the Adoption of Neuromarketing in Major Spanish Corporations - Crespo-Pereira, Verónica; Legerén-Lago, Beatriz; Arregui-McGullion, Jaime (Frontiers in Communication, 2020)
Technological advances in the field of neuroscience have been well received in the entertainment and advertising industries, where there are great commercial benefits linked to knowing the most intimate aspects of how audiences and consumers respond to different messages. Large enterprises seem to resist implementing them in their marketing activities, thus limiting the development of the discipline. This research reflects on the main factors that impact the adoption of neuromarketing within large companies, both from a bibliographical and an empirical perspective. . A review of secondary sources was undertaken to understand the current state of neuromarketing and its place within large-scale enterprises. This review suggested that a series of internal and external factors may be limiting its adoption. To validate the results of the bibliographical research, a structured, self-administered online questionnaire was designed. The aims of this survey were to diagnose the level to which major corporations in Spain are aware of and employ neuromarketing; and to identify the internal and external factors that may be limiting or driving its rate of adoption. A pilot test was undertaken to validate the sampling methods and survey distribution strategy and to measure the impact of some major challenges that had been identified during survey design. The pilot study did succeed in reaching highly qualified respondents, but its low response rate highlighted a major issue in the research design: the sampling method cannot scale efficiently. A full review of the sampling strategy and survey distribution method is needed before a full-scale study can be launched. The data gathered in the pilot study can´t be considered representative or statistically valid; they are, at best, preliminary findings that will need to be validated by further research. Responses do suggest that neuromarketing techniques are not used in the majority of large Spanish companies and that the level of knowledge on the subject is not very high. Neuromarketing seems to have a good reputation amongst industry practitioners and its adoption seems likely to increase in the future. Further research in this area should take into account the learnings provided by this pilot.